ESP LEARNERS’ PERCEPTIONS ON USING DUOLINGO - Haya Haratikka; Anita Purba (RADJA PUBLIKA, 2024)
The implementation of techology in education was really helpful. The development of technology has increased the number of intriguing and fresh online resources for English learning. The Duolingo app makes learning languages, particularly English, simple, convenient, and efficient. The presence of Duolingo app offered ESP learners to learn basic English independently. There were several previous researches which explore more about the use of Duolingo for learning language, particularly English. Therefore the aim of this research was to see and analyze ESP learners’ opinion on the implementation of Duolingo in order to strengthen their basic English. This was a qualitative research which took sixtyone ESP learners as the informants. The data of this study was ESP learners answers on the use of Duolingo. The data were gainned by distributing an online and open ended questionaires to ESP learners who took randomnly. The findings were ESP learners enjoyed learning basic English through the exercised offered by Duolingo. Because its offering to practice English skills in daily. Then, they can learn English as if they learn with the real native speakers. The Duolingo program allows students to acquire vocabulary in English, which includes in several features such as gamification.